THE POTENTIAL OF TANGGOMO ORAL LITERATURE IN DEVELOPING CULTURAL OBJECT AND TOURIST ATTRACTIONS IN GORONTALO UTARA REGENCY - Sance A. Lamusu (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2020)
The general objective of this research is to realize the potential of Tanggomo oral literature in supporting the development of cultural objects and tourist attractions in Gorontalo Utara District. The specific objective of this research is to design a strategy that can produce local government policies, especially in Gorontalo Utara District, in terms of turning the Tanggomo oral literature into the development of cultural objects and tourist attractions. This study employed a descriptive-qualitative method and literary ecology and cultural ecology approaches. The results showed that Tanggomo oral literature has the potential to become a cultural object and a tourist attraction due to several supporting factors, namely: (1) the Tanggomo functions in complementing the life of the Gorontalo people; (2) the Tanggomo functions as enlightenment for the audience; (3) the Tanggomo is one of the performing oral literature; (4) the Tanggomo contains literary ecology and cultural ecology; (5) the Tanggomo tells about various themes such as history, customs, life experiences of a person, important events, the origin of a certain place, and so on; (6) the Tanggomo functions as an entertainer; and (7) the Tanggomo can be performed and recited by children, adolescents, or adults.